1992
DOI: 10.1073/pnas.89.1.373
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor inhibits growth of hepatocellular carcinoma cells.

Abstract: Hepatocyte growth factor (HGF) is a potent mitogen for primary hepatocytes. Therefore, we examined HGF as a possible autocrine growth factor in hepatocellular carcinoma (HCC). We introduced an albumin-HGF expression vector into Fao HCC cells and transgenic mice. Expression of the albumin-HGF vector in Fao HCC cells inhibited their growth in vitro. In vivo, FaoHGF cells produced tumors that averaged 10% of the sizes of G418-resistant controls when transplanted into nude mice. In contrast, hepatocytes from trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
151
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(168 citation statements)
references
References 25 publications
(25 reference statements)
14
151
2
1
Order By: Relevance
“…It has been reported that HGF inhibits the growth of various hepatoma cell lines in vitro 39 and in vivo. 40 Shiota et al demonstrated that no liver tumors occurred in HGF transgenic mice for more than 18 months. 15 In contrast, Sakata et al recently reported that more than half of the HGF transgenic mice studied above 17 months of age developed benign and/or malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HGF inhibits the growth of various hepatoma cell lines in vitro 39 and in vivo. 40 Shiota et al demonstrated that no liver tumors occurred in HGF transgenic mice for more than 18 months. 15 In contrast, Sakata et al recently reported that more than half of the HGF transgenic mice studied above 17 months of age developed benign and/or malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts to find substances that inhibit the activation of c-Met are thus expected to lead to suppression of the malignant transformation of cells. However, HGF has an opposing effect on the regulation of cell proliferation in accordance with cell type: it promotes the proliferation of some tumor cells, but suppresses that of others (3,4). This opposing effect is considered to depend on differences in the downstream pathways of c-Met (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…However, HGF has an opposing effect on the regulation of cell proliferation in accordance with cell type: it promotes the proliferation of some tumor cells, but suppresses that of others (3,4). This opposing effect is considered to depend on differences in the downstream pathways of c-Met (3)(4)(5). Thus, elucidation of the pathways responsible for the effect is expected to lead to new drugs for the suppression of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, studies using human HCC cell lines in vitro show that HGF-SF inhibits cells growth. 11,12 Similarly, in animal studies in which HCC is induced using diethylnitrosamine, infusion of HGF resulted in decreased cell proliferation by up to 50%. 13 HGF-SF has also been reported to induce proapoptotic genes in human HCC cells in culture.…”
mentioning
confidence: 99%